Sistem Informasi Administrasi Pengelolaan Barang Habis Pakai Di UPT Teknologi Informasi Dan Komunikasi Universitas Sebelas Maret Surakarta - Nugroho, Sigit; Pantjarani, Ari; Naury, Chairullah (Politeknik Harapan Bangsa Surakarta, 2024)
Information systems are needed by an agency, both private and government agencies. Sebelas Maret University Surakarta (UNS) is a government agency engaged in higher education. Operational activities in each activity system at UNS require consumables, to manage data and information needed by students when attending lectures. Data recording of income, expenditure and stock of consumables at UPT Information and Communication Technology UNS still uses the manual method, using the Microsoft Excel application. Data recording of consumables and the current reporting process are considered less effective. This is because the initial process of data entry uses notes in the book and then it is copied to the Microsoft Excel application. A process like this takes a long time, besides that if you need last month's data you have to search one by one because the file is still random. Based on the description of the background, it can be formulated that the problem to be solved in this research is